Some applications for generalized fractional operators in analytic functions spaces - Adem, Kilicman; Abdulnaby, Zainab E. (The Kangwon-Kyungki Mathematical Society, 2019)
In this study a new generalization for operators of two parameters type of fractional in the unit disk is proposed. The fractional operators in this generalization are in the Srivastava-Owa sense. Concerning with the related applications, the generalized Gauss hypergeometric function is introduced. Further, some boundedness properties on Bloch space are also discussed.